Stability assessment of underground parking cavern in Hammerfest - Pettersen, Martin Dyhrberg (NTNU, 2014)
This thesis addresses in detail the stability of the planned parking cavern in Hammerfest. It includes a review on recognized literature of support design for underground constructions, frost issues in tunnels, water inflow and mitigation, numerical modelling, and general stability of underground caverns. Studying the local and regional geology reviled that the rock mass is mainly composed of gneiss, with some small amount of quartzite. The rock mass is expected to be strong (RMR>60, Q>10) but encountering a zone of weak rock mass(Q<0.01) is anticipated. Two cases of underground facilities in Norway are reviewed with emphasis on key experiences, support requirement, and monitoring. Support needed for the Hammerfest parking cavern is suggested by analytical, empirical approaches. Finalized rock support measures are quantified and tested with numerical modelling. The cavern is expected to be sufficiently supported with rock bolts and shotcrete. However, if weak rock is encountered, reinforced shotcrete arches and spiling bolts will be needed. Kinematic assessment is carried out identifying possible failing wedges in the roof and walls. Leakage of water is discussed and consequences of draining surface ponds are evaluated. Some leakage is expected in the cavern based on field observations however, levels are generally anticipated as dripping. Ahead-of-face investigations are concluded necessary to identify possible high water conduction near the weak rock mass zone. There will be need for grouting should the water leakage exceed quantified limits given in the thesis. Frost intrusion to the cavern is modelled and discussed. It has been recognized that frost will enter the cavern and sufficient mitigation is suggested.